Evaluation of bonding agent application on concrete patch performance - Donjuan, Jose (Kansas State University, 2014)
The durability of partial depth concrete repair is directly related to the bond strength between the repair material and existing concrete. The wait time effects of cementitous grouts, epoxy, acrylic latex, and polyvinyl acetate bonding agents were observed on bond strength. Three rapid repair materials were as a comparison to bond strength, as well as concrete samples with no bonding agents having dry conditions and saturated surface dry moisture condition. The bonding agents and rapid repair materials were tested in a controlled laboratory environment. Bond strength loss with wait times of 0, 2, 5, 10, and 30 minutes were observed when bonding agents were applied. The laboratory samples were loaded using a direct shear test. Field tests were performed using the same repair materials and bonding agents. When the agents were applied in the field the wait times used were 0, 15, 30, and 45 minutes. 7 day and 5 month pull off tensile tests were performed during the field experiment. The data from both experiments show that when using cement grout bonding agents the high bond strength can be obtained when the repair material is applied within 15 minutes of application of the cement grout, and after 15 minutes bond loss can be expected. Wait time didn't have a significant effect on epoxy and acrylic latex bonding agents as long as they were placed before setting. The polyvinyl acetate agent and repair materials can develop high bond strength in laboratory settings, but when used in the field the bond strengths experience loss. When not using bonding agents in a repair, adequate bond strength can be obtained when using saturated surface dry condition.
Keywords: concrete patch repair; Bonding agents; Shear stress; Tensile stress; Civil Engineering (0543)